FIGURATIVE MEANINGS IN SECONDHAND SERENADE’S SONG LYRICS - Marina Lestari; Muhammad Natsir (State University of Medan, 2015)
The study deals with the Figurative meanings that consist of hyperbole, simile,metaphor, personification, and symbol. The objectives of this research were tofind out the types of figurative meanings used in Secondhand Serenade’s songlyrics and to describe the dominant one type of figurative meanings. This researchwas conducted by using qualitative method. The sources of the data were albumsand lyrics of Secondhand Serenade and the data were 67 sentences of secondhandserenade’s song lyrics. After analyzing, it was found that there were 67 sentencesof Secondhand Serenade’s song lyrics. The findings of this research were foundthat 30 (44.77%) hyperbole, 14 (20.89%) symbol, 11 (16.41%) simile, 7 (10.44%)metaphor, and 5 (7.46%) personification. Hyperbole 30(44.77%) becomes thedominant type of figurative meanings in secondhand serenade’s song lyrics.